Revisiting the notion of political black cinema: A comparative analysis of Melvin Van Peebles and Ousmane Sembene. (1st April 2013) - Ryan, Connor
This article revisits Ousmane Sembene's La Noire de ... (1966) and Melvin Van Peebles's Sweet Sweetback's Baaadasssss Song (1971) to put pressure on Sembene's legacy as an advocate of African women's rights and Van Peeble's reputation as a provocative voice in the American Black Arts Movement. Focusing on each films' defiant yet silent protagonists, this article questions feminism's concern for women to speak out against patriarchy that would silence them. It asks whose liberation the films provide for, and interrogates cinema that speaks for the voiceless. This article posits that artistic voice, even when mobilized for political resistance, always presents a risk and threat of displacing violence. Speaking out against oppression, whether white supremacist, neo-imperialist or patriarchal oppression, requires the speaker to wield a certain authority that invests in other means of oppression. This article addresses the politically committed artist's responsibility to navigate the tenuous relationship between politics and art.